Search for the minimum thermal conductivity in mixed cryocrystals (CH₄)₁₋ξ Krξ - Konstantinov, V.A.; Manzhelii, V.G.; Revyakin, V.P.; Pohl, R.O. (Физика низких температур, 2001)
The isochoric thermal conductivity of (CH4)1-ξ Krξ solid solutions is studied between 40 K and ~ 150 K

over the wide range of concentrations (ξ = 0.013, 0.032, 0.07, 0.115, 0.34, 0.71, 0.855,

0.937, and 0.97). A gradual transition from the thermal conductivity of a highly perfect

crystal to the minimum thermal conductivity is observed as the crystal becomes increasingly

more disordered. A qualitative description is given in the framework of Debye model of

thermal conductivity, which takes into consideration the fact that phonon mean free path

cannot decrease indefinitely.